Data Aggregation in Wireless Sensor Networks - Luo, Li (International Journal of Online and Biomedical Engineering (iJOE), 2016)
In order to solve the problem of low efficiency and high energy consumption in data processing, In this paper, for reducing the communication overhead of data aggregation, we put forward a cluster division based data aggregation scheme for wireless sensor networks in which the cluster is divided into three subareas and some report nodes are assigned to each subarea. Simulation results show that, compared with LEACH algorithm, BP neural network and PSO-BP algorithm, more than 50% lower compression error is decreased and the simplicity of the improved algorithm makes it suitable for massive and the long term environmental monitoring network.